Posthumanism in The Windup Girl: Blurring Boundaries between Human and Machine - Acharya, Sharad (Exploration अन्वेषण, 2026)
This study examines Paolo Bacigalupi's The Windup Girl through a post-humanist lens, focusing on the ethical, social, and philosophical implications of blurred boundaries between humans and technologically engineered beings. Emiko, a genetically modified "Windup," embodies posthuman hybridity and becomes a site of contestation in a world shaped by biopolitics, ecological decline, and techno-capitalist domination. Her experiences of exploitation, marginalisation, and emergent agency reveal the complexities of posthuman subjectivity. Drawing on theorists such as Donna Haraway, N. Katherine Hayles, Ray Kurzweil, and David Gunkel, this qualitative textual analysis interrogates how human–cyborg relationships destabilise fixed categories of identity, morality, and empathy. The findings suggest that the novel presents a powerful critique of species hierarchy, ethical responsibility, and human exceptionalism, urging readers to reconsider moral obligations toward technologically mediated life. Ultimately, The Windup Girl illuminates the entanglement of humanity, technology, and environment in an increasingly posthuman future.